PERTUMBUHAN DAN HASIL SEMBILAN KULTIVAR KEDELAI (Glycine max (L.) Merill) DALAM SISTEM TANAM TUMPANGSARI DENGAN JAGUNG MANIS (Zea mays Saccharata Strut) - Lupi Anggraeni; Umi Trisnaningsih; Siti Wahyuni (Agroswagati Jurnal Agronomi, 2020)
Soybean cultivation can be done in monoculture or intercropping systems. The purpose of this study was to determine the growth and yield of soybean (Glycine max (L.) Merill) on intercropping with sweet corn (Zea mays Saccharata). This experiment was carried out in Getasan Village, Depok District, Cirebon Regency, from April to July 2019. The experimental method used was Randomized Complete Block Design (RCBD), with cultivars as treatments. The treatments consisted of nine soybean cultivars, namely: Agromulyo, Anjasmoro, Baluran, Burangrang, Dega 1, Ring 1, Devon 1, Grobogan, and Willis. The plot size used is 2m x 3m. Soybean spacing is 25 cm x 25 cm, whereas sweet corn is 75 cm x 25 cm. Corn is planted 10 days after planting soybeans. The results showed that there were significant effects of nine cultivars intercropped with sweet corn on the variables tested, except for the number of trifoliate leaves, stem diameter and leaf area. Grobogan's cultivar soybeans gave better growth and yields than other cultivars with a dry seed weight of 2.07 kg plot-1.